2013
DOI: 10.1371/journal.pone.0067133
|View full text |Cite
|
Sign up to set email alerts
|

Life Expectancy and Death by Diseases of the Circulatory System in Patients with Bipolar Disorder or Schizophrenia in the Nordic Countries

Abstract: ObjectiveExcess mortality from diseases and medical conditions (natural death) in persons with psychiatric disorders has been extensively reported. Even in the Nordic countries with well-developed welfare systems, register based studies find evidence of an excess mortality. In recent years, cardiac mortality and death by diseases of the circulatory system has seen a decline in all the Nordic countries, but a recent paper indicates that women and men in Denmark, Finland, and Sweden, who had been hospitalised fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
203
2
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 276 publications
(215 citation statements)
references
References 35 publications
6
203
2
4
Order By: Relevance
“…SMR for both sexes was higher in patients admitted in 1998-2006 versus those admitted in 1980-1988 (Høye et al 2011). In another Scandinavian study results from observations in 2000-2007 were unambiguous: SMR was 3.3, 3.0, and 2.9 for men, and 3.9, 2.7 and 2.9 for women in Finland, Denmark and Sweden, respectively (Laursen et al 2013). …”
Section: Sexmentioning
confidence: 92%
See 3 more Smart Citations
“…SMR for both sexes was higher in patients admitted in 1998-2006 versus those admitted in 1980-1988 (Høye et al 2011). In another Scandinavian study results from observations in 2000-2007 were unambiguous: SMR was 3.3, 3.0, and 2.9 for men, and 3.9, 2.7 and 2.9 for women in Finland, Denmark and Sweden, respectively (Laursen et al 2013). …”
Section: Sexmentioning
confidence: 92%
“…Scandinavian studies showed that in Finland and Denmark in schizophrenia patients, SMR associated with cardiovascular diseases was lower than all causes of death in total. However, when ischaemic heart disease, cerebrovascular disease and other cardiovascular diseases (including rheumatic heart disease, hypertension, arterial or venous diseases) were considered separately, no significant SMR deviations were demonstrated in Denmark and Sweden, while in Finland that rate was higher for other cardiovascular diseases (Laursen et al 2013). …”
Section: Cardiovascular Diseasesmentioning
confidence: 93%
See 2 more Smart Citations
“…The vast majority (in excess of 70%) of the premature mortality observed in people with affective disorders is due to physical comorbidities, predominantly cardio-metabolic diseases (Wulsin et al, 1999, Laursen et al, 2013. People with affective disorders are at greatly increased risk of metabolic syndrome (Vancampfort et al, 2013a;Vancampfort et al, 2014) and type 2 diabetes mellitus (T2DM) (Vancampfort et al, 2015a & b).…”
Section: The Prevalence and Burden Of Metabolic Disease In People Witmentioning
confidence: 99%